Pemanfaatan Limbah Ampas Kopi menjadi Pupuk Organik - Ilham, Muhammad Maulana; Anggraini, Dewi; Yofinaldi, Septian; Wirayuda, Rangga (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Coffee shop is one of the popular places that is often visited by various groups, both young people, adults and even the elderly and is a comfortable choice to just hangout, do assignments or even hold client meetings. With the increasing popularity of their Coffee shop, they have more branches and have many places with new names. As a result, there will be more Coffee waste such as plastic waste and Coffee grounds waste. Therefore, it is necessary to develop and utilize recycling so that it does not cause waste. Unlike most Coffee shops, less waste more Coffee they have the appeal of not using plastic or 0% plastic and recycling used Coffee grounds into plant fertilizer. This is a good innovation so that the Coffee shop which initially had waste and garbage became 0% waste. And Coffee grounds waste but can be overcome by being used as plant fertilizer so that it can be of added value and can be useful for nature and the surrounding environment. This needs to be applied to other cafe Shops in order to maximize value by utilizing waste.